2022
DOI: 10.3389/fpubh.2022.861463
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adolescents' Dietary Behaviors in the School and Home Environment in Addis Ababa, Ethiopia

Abstract: BackgroundMalnutrition affects many adolescents in Ethiopia. Over one-third of adolescent girls and two-thirds of boys are thin. Overweight and obesity in Ethiopia is mostly a concern in urban populations of higher wealth quintiles. Urbanization and globalization of diets is shifting food environments. The objective of this study was to assess whether food environments in and around schools in urban Ethiopia influence dietary diversity, quality, BMI status or perceptions of adolescents.MethodsTwelve high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
1
4
0
1
Order By: Relevance
“…Diet quality was higher among students in households with high income compared with students in low-income households. This finding was supported by studies in Ethiopia, Turkey, and Japan that showed good-quality diets among adolescents in households with better income than adolescents in poor households 8 48 49. This could be due to the fact that wealthy people have a better purchasing power of diversified foods than those who are less wealthy 50.…”
Section: Discussionmentioning
confidence: 66%
“…Diet quality was higher among students in households with high income compared with students in low-income households. This finding was supported by studies in Ethiopia, Turkey, and Japan that showed good-quality diets among adolescents in households with better income than adolescents in poor households 8 48 49. This could be due to the fact that wealthy people have a better purchasing power of diversified foods than those who are less wealthy 50.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study found that daily consumption of sweetened beverages was associated with increased prevalence of overweight and obesity in students (Hu et al , 2023). Also, Trübswasser et al (2022) reported that most teenagers spent their pocket money on sweetened beverages, sweets or fried foods; another study stated that adolescents bought and consumed large amounts of ultra-processed foods and beverages at school while they are with their peers (Rocha et al , 2023). Also, Kleiser et al (2009) found that higher consumption of high-calorie snacks and junk foods, such as sweetened beverages and sausages, were associated with childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, neste estudo, a autopercepção negativa de saúde foi mais prevalente em adolescentes com consumo de frutas adequado. Estudo mostra que adolescentes são mais propensos a gastar dinheiro com frituras, doces ou refrigerantes do que com frutas (Trübswasser et al, 2022). Este estudo apresenta resultados relevantes devido à formação do conhecimento em saúde dos adolescentes nesse período da vida e ao seu papel na promoção da saúde e dos comportamentos saudáveis.…”
Section: Discussionunclassified